2022
DOI: 10.1021/acsami.2c11775
|View full text |Cite
|
Sign up to set email alerts
|

Highly Transparent Polycrystalline MgO via Spark Plasma Sintering

Abstract: Optically transparent ceramics and MgO in particular are promising materials for a wide range of optical applications. This study introduces exceptionally highly transparent MgO ceramics produced via spark plasma sintering (SPS) at relatively low temperature and pressure by optimal incorporation of LiF as a sintering additive. The effect of LiF content on the microstructural and optical properties is presented with emphasis on its function as a densification aid and an agent for minimizing residual carbon cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The main carbon source in the SPS process is the carbon foil that is placed within the graphite mold to protect it. In a previous study of the carbon foils, a considerable weight loss was observed, which was associated with CO 2 release when performing simultaneous thermogravimetric analysis (TGA) and mass spectroscopy in Ar in the temperature range of 800 °C–1300 °C …”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The main carbon source in the SPS process is the carbon foil that is placed within the graphite mold to protect it. In a previous study of the carbon foils, a considerable weight loss was observed, which was associated with CO 2 release when performing simultaneous thermogravimetric analysis (TGA) and mass spectroscopy in Ar in the temperature range of 800 °C–1300 °C …”
Section: Resultsmentioning
confidence: 98%
“…Nevertheless, SPS is typically performed in a carbon-rich environment (e.g., using graphite tools and molds) to ensure electrical conduction. Consequently, samples are susceptible to carbon contamination, which considerably impairs their optical transparency. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPS rapidly heats the materials under uniaxial pressure to produce high density ceramics. The ability to apply very high heating and cooling rates, short residenc times, and sintering at relatively low temperatures limits grain growth during densifica tion [54]. SPS can be categorized as a low-temperature sintering technique, and the prin ciple of discharge plasma sintering is shown in Figure 4 [55].…”
Section: Spark Plasma Sinteringmentioning
confidence: 99%